Rosemary (Rosmarinus officinalis) Extract Modulates CHOP/GADD153 to Promote Androgen Receptor Degradation and Decreases Xenograft Tumor Growth - Petiwala, Sakina M.; Berhe, Saba; Li, Gongbo; Puthenveetil, Angela G.; Rahman, Ozair; Nonn, Larisa; Johnson, Jeremy J. (PLOS ONE, 2014)
The Mediterranean diet has long been attributed to preventing or delaying the onset of cardiovascular disease, diabetes and various solid organ cancers. In this particular study, a rosemary extract standardized to carnosic acid was evaluated for its potential in disrupting the endoplasmic reticulum machinery to decrease the viability of prostate cancer cells and promote degradation of the androgen receptor. Two human prostate cancer cell lines, 22Rv1 and LNCaP, and prostate epithelial cells procured from two different patients undergoing radical prostatectomy were treated with standardized rosemary extract and evaluated by flow cytometry, MTT, BrdU, Western blot and fluorescent microscopy. A significant modulation of endoplasmic reticulum stress proteins was observed in cancer cells while normal prostate epithelial cells did not undergo endoplasmic reticulum stress. This biphasic response suggests that standardized rosemary extract may preferentially target cancer cells as opposed to “normal” cells. Furthermore, we observed standardized rosemary extract to decrease androgen receptor expression that appears to be regulated by the expression of CHOP/GADD153. Using a xenograft tumor model we observed standardized rosemary extract when given orally to significantly suppress tumor growth by 46% compared to mice not receiving standardized rosemary extract. In the last several years regulatory governing bodies (e.g. European Union) have approved standardized rosemary extracts as food preservatives. These results are especially significant as it is becoming more likely that individuals will be receiving standardized rosemary extracts that are a part of a natural preservative system in various food preparations. Taken a step further, it is possible that the potential benefits that are often associated with a “Mediterranean Diet” in the future may begin to extend beyond the Mediterranean diet as more of the population is consuming standardized rosemary extracts.